Modified fluororubber with high mechanical property, preparation method and fluororubber sealing ring
By adding modified oxidation to fluorine rubber and adopting specific preparation methods, the problem of poor mechanical properties of fluorine rubber sealing rings is solved, significantly improved its high temperature resistance and tensile stretching performance, and enhanced its application value.
Patent Information
- Application Number
- CN202410820664.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-24
- Publication Date
- 2025-01-28
AI Technical Summary
The mechanical properties of existing fluoroelastic seals are poor, limiting their application in high temperature, high pressure and corrosive media environments.
By adding modified oxidation to fluorine rubber, and using specific preparation methods, including drying, mixed, vulcanization and other steps, the mechanical properties of fluorine rubber are improved.
It significantly improves the mechanical properties of fluorine rubber sealing rings, including high temperature resistance and tensile stretching performance, and enhances its application value in the environment of high temperature, high pressure and corrosive media.
Smart Images

Figure CN119371836A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a modified fluororubber with high mechanical properties, a preparation method and a fluororubber sealing ring. Background Art
[0002] Perfluoroether sealing ring is a sealing material used in high temperature, high pressure and corrosive media environment. Its manufacturing involves chemical engineering, material science and engineering. Perfluoroether has excellent chemical corrosion resistance, high temperature stability and excellent sealing performance, so it is widely used in petrochemical, aerospace, medicine and other fields. In addition to the above properties, mechanical properties are also one of the important indicators for evaluating the performance of perfluoroether sealing ring.
[0003] The invention patent with patent application number CN201811130905.5 discloses a PTFE fluoropolymer O-ring and its production process. The O-ring prepared by molding method has the superior properties of wear resistance, pressure resistance, high temperature resistance and oil resistance by using fluororubber as the main rubber system, adding polytetrafluoroethylene powder and a filling system composed of carbon black and inorganic fillers reasonably matched. However, the high temperature compression deformation of PTFE powder is not ideal, and the tensile strength is not high.
[0004] The invention patent with patent application number CN202311728618.5 discloses a process for improving the deformation rate of the sealing ring of a cylindrical lithium battery helmet. By using a reinforcing agent, the tensile and extrusion resistance of the sealing ring can be improved. By adding an antioxidant, the antioxidant capacity of the sealing ring can be improved, and the deformation of the sealing ring caused by changes in the external environment during use can be alleviated. By using adhesives and retardants, the utilization of raw materials can be improved, and the prepared sealing ring material can be promoted to improve the cross-linking effect between the raw materials. However, the mechanical properties of this invention are relatively low.
[0005] The invention patent with patent application number CN202310429726.6 discloses a modified fluororubber sealing ring and a preparation method thereof. The temperature resistance of the sealing ring is improved by mixing aramid pulp, a resin composition, diisopropylbenzene peroxide, a reinforcing agent and a stabilizer, but there is no significant improvement in the mechanical properties of the sealing ring.
[0006] The fluororubbers prepared by the above methods all have the defect of poor mechanical properties, which limits their further application. Therefore, it is urgent to design and develop a method for preparing a fluororubber sealing ring with good mechanical properties. Summary of the invention
[0007] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a modified fluororubber with high mechanical properties, a preparation method and a fluororubber sealing ring.
[0008] The technical solution adopted by the present invention is as follows:
[0009] The first aspect of the present invention provides a modified fluororubber with high mechanical properties, which comprises the following components in parts by weight:
[0010] Fluororubber 80-120 parts by mass;
[0011] 5-30 parts by mass of modified yttrium oxide;
[0012] Internal release agent 0-8 parts by mass;
[0013] Acid absorbent 0-10 parts by weight;
[0014] Accelerator 0-8 parts by weight;
[0015] Vulcanizing agent 0-8 parts by weight;
[0016] The modified yttrium oxide is obtained by modifying yttrium oxide with a modifier, and the modifier includes one or more of TEOS, zinc oxide, and PFPE.
[0017] Preferably, the modifier includes zinc oxide and PFPE.
[0018] Preferably, the modifier includes TEOS, zinc oxide, and PFPE.
[0019] Preferably, the preparation of the modified yttrium oxide comprises the following steps:
[0020] S1. Dissolving yttrium oxide in a solvent to obtain a mixed solution L1;
[0021] S2. Add aqueous ammonia to the mixed solution L1 and stir for 0-1h to obtain a mixed solution L2;
[0022] S3. Add zinc oxide to the mixed solution L2 and stir at 50-70 ° C for 1-3 h to obtain a mixed solution L3;
[0023] S4. Add PFPE to the mixed solution L3 and stir at 80-120°C for 20-28h to obtain a mixed solution L4;
[0024] S5. TEOS was added to the mixed solution L4 and stirred at 30-60°C for 4-8h to obtain a mixed solution L5;
[0025] S6. Wash, centrifuge and dry the mixed solution L5 to obtain modified yttrium oxide.
[0026] Preferably, the mass volume ratio of zinc oxide, PFPE and TEOS is 1:8-12:8-12.
[0027] Preferably, the fluororubber is perfluoroether rubber, and the perfluoroether rubber is at least one of peroxide perfluoroether rubber, triazine perfluoroether rubber, and the like.
[0028] Preferably, the internal mold release agent is one or more of HT290 and WS280; the acid absorber is one or more of zinc oxide, magnesium oxide, and sodium hydroxide; the vulcanizing agent is one or more of dipentadienyl, triazine trithiol tetrabutylammonium salt, and BOAP. The internal mold release agent can improve the demoulding effect of the product (sealing ring).
[0029] Preferably, it comprises the following components in parts by weight:
[0030] 100 parts by mass of fluororubber;
[0031] 10 parts by mass of modified yttrium oxide;
[0032] 1 part by mass of internal release agent;
[0033] 3 parts by mass of acid absorbent;
[0034] 2 parts by mass of accelerator;
[0035] 1 part by mass of vulcanizing agent.
[0036] A second aspect of the present invention provides a method for preparing the modified fluororubber as described above, characterized in that it comprises the following steps:
[0037] (1) Weigh the raw materials according to mass fraction;
[0038] (2) drying the raw materials in step (1), adding them into an open mill and mixing them at a mixing temperature of 35-75° C., and mixing them evenly to obtain a rubber compound;
[0039] (3) subjecting the rubber compound obtained in step (2) to a curing process in a vulcanizer at a temperature of 155-205° C. for a time of 8-12 min;
[0040] (4) The material obtained by vulcanization in step (3) is placed in a blast oven for two-stage vulcanization at a vulcanization temperature of 185-305° C. and a vulcanization time of 8-24 h.
[0041] A third aspect of the present invention provides a fluororubber sealing ring, the main material of which is the modified fluororubber as described above.
[0042] The beneficial effects of the present invention are as follows: the present invention adopts modified yttrium oxide to improve the mechanical properties of fluororubber, and the prepared fluororubber has good high temperature resistance and high market application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.
[0044] Figure 1 The infrared test images of the samples obtained in Examples 1-3 and Comparative Example 1;
[0045] Figure 2 The performance test results of samples obtained for Examples 1-6 and Comparative Example 1;
[0046] Figure 3 Scanning electron microscope images of samples obtained for Examples 1-3 and Comparative Example 1. DETAILED DESCRIPTION
[0047] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0048] Example 1
[0049] S1, 5 g of yttrium oxide, 100 g of water and 500 g of ethanol were mixed, and stirred with a magnetic stirrer for 30 min to obtain a mixed solution L1;
[0050] S2, add 5 ml of ammonia water to the mixed solution L1 and stir for 20 min to obtain a mixed solution L2;
[0051] S3, add 5 ml of TEOS to the mixed solution L2, stir at 45°C for 6 hours to obtain a mixed solution L3;
[0052] S4, washing, centrifuging and drying the mixed solution L3 to obtain modified yttrium oxide;
[0053] S5. Weigh 100 parts of perfluoroether rubber, 10 parts by mass of modified yttrium oxide, 1 part by mass of internal mold release agent, 3 parts by mass of acid absorber, 2 parts by mass of accelerator, and 1 part by mass of vulcanizing agent;
[0054] S6, adding the rubber weighed in S5, modified yttrium oxide, internal mold release agent, acid absorber, accelerator, and vulcanizer to an open mill for mixing, the mixing temperature is 30-70° C., preferably 55° C., and mixing is uniform;
[0055] S7, vulcanizing the rubber mixture obtained in S6 into a sealing ring and a long sheet in a vacuum vulcanizer at a vulcanizing temperature of 170° C. for 10 min;
[0056] S8. Place the sealing ring obtained in S7 in a blast oven for two-stage vulcanization at a vulcanization temperature of 230°C for 16 hours. The obtained sample is recorded as M1. The infrared test results are as follows: Figure 1 , the electron microscope image of the tensile fracture is as follows Figure 3 ;
[0057] S9. The obtained sealing ring and long sheet were tested for performance. The compression permanent deformation was tested according to ASTM D395 method B, and the tensile test was tested according to the method in ASTM D412. The test results are shown in Figure 2 .
[0058] Example 2
[0059] S1, 5 g of yttrium oxide, 100 g of water and 500 g of ethanol were mixed, and stirred with a magnetic stirrer for 30 min to obtain a mixed solution L1;
[0060] S2, add 5 ml of ammonia water to the mixed solution L1 and stir for 20 min to obtain a mixed solution L2;
[0061] S3, add 0.5 g zinc oxide to the mixed solution L2, stir at 60° C. for 2 h, and obtain a mixed solution L3;
[0062] S4, adding 5 g of PFPE to the mixed solution L3, stirring at 100° C. for 24 h to obtain a mixed solution L4;
[0063] S5, washing, centrifuging and drying the mixed solution L4 to obtain modified yttrium oxide;
[0064] S6. Weigh 100 parts of perfluoroether rubber, 10 parts by mass of modified yttrium oxide, 1 part by mass of internal mold release agent, 3 parts by mass of acid absorber, 2 parts by mass of accelerator, and 1 part by mass of vulcanizing agent;
[0065] S7, adding the rubber weighed in S6, modified yttrium oxide, internal mold release agent, acid absorber, accelerator, and vulcanizer to an open mill for mixing, the mixing temperature is 30-70° C., preferably 55° C., and mixing is uniform;
[0066] S8, vulcanizing the rubber mixture obtained in S7 into a sealing ring and a long sheet in a vacuum vulcanizer at a vulcanizing temperature of 170° C. for 10 min;
[0067] S9, put the sealing ring obtained in S8 in a blast oven for two-stage vulcanization, the vulcanization temperature is 230℃, the vulcanization time is 16h, and the obtained sample is recorded as M2. The infrared test results are as follows Figure 1 , the electron microscope image of the tensile fracture is as follows Figure 3 ;
[0068] S10, the obtained sealing ring and long sheet were tested for performance, the compression permanent deformation was tested according to ASTM D395 method B, and the tensile test was tested according to the method in ASTM D412. The test results are shown in Figure 2 .
[0069] Example 3
[0070] S1, 5 g of yttrium oxide, 100 g of water and 500 g of ethanol were mixed, and stirred with a magnetic stirrer for 30 min to obtain a mixed solution L1;
[0071] S2. Add 5 ml of aqueous ammonia to the mixed solution L1 and stir for 20 min to obtain a mixed solution L2.
[0072] S3. Add 0.5 g of zinc oxide to the mixed solution L2, stir at 60° C. for 2 h, and obtain a mixed solution L3.
[0073] S4. Add 5 g of PFPE to the mixed solution L3, stir at 100° C. for 24 h, and obtain a mixed solution L4.
[0074] S5. Add 5 ml of TEOS to the mixed solution L4, stir at 45°C for 6 h to obtain a mixed solution L5.
[0075] S6. Wash, centrifuge and dry the mixed solution L5 to obtain modified yttrium oxide.
[0076] S7. Weigh 100 parts of perfluoroether rubber, 10 parts by mass of modified yttrium oxide, 1 part by mass of internal mold release agent, 3 parts by mass of acid absorber, 2 parts by mass of accelerator, and 1 part by mass of vulcanizing agent.
[0077] S8, adding the rubber weighed in S7, modified yttrium oxide, internal mold release agent, acid absorber, accelerator and vulcanizer to an open mill for mixing, the mixing temperature is 35-75°C, preferably 55°C, and the mixing is uniform.
[0078] S9. The mixed rubber obtained in S2 is vulcanized into a sealing ring and a long sheet in a vacuum vulcanizer at a vulcanization temperature of 170° C. and a vulcanization time of 10 min.
[0079] S10, put the sealing ring obtained in S3 into a blast oven for two-stage vulcanization, the vulcanization temperature is 230℃, the vulcanization time is 16h, and the obtained sample is recorded as M3. The infrared test results are as follows Figure 1 , the electron microscope image of the tensile fracture is as follows Figure 3 S11. The obtained sealing ring and long sheet were tested for performance. The compression set was tested according to ASTM D395 method B, and the tensile test was tested according to the method in ASTM D412. The test results are shown in Figure 2 .
[0080] Example 4
[0081] The difference between this embodiment and embodiment 3 is that in step S7, 5 parts by mass of modified yttrium oxide are weighed, and the sample finally obtained is recorded as M4.
[0082] Example 5
[0083] The difference between this embodiment and embodiment 3 is that in step S7, 20 parts by mass of modified yttrium oxide are weighed, and the sample finally obtained is recorded as M5.
[0084] Example 6
[0085] The difference between this embodiment and embodiment 3 is that in step S7, 30 parts by mass of modified yttrium oxide are weighed, and the sample finally obtained is recorded as M6.
[0086] Comparative Example 1
[0087] S1. Weigh 100 parts by mass of perfluoroether rubber, 10 parts by mass of yttrium oxide, 1 part by mass of internal mold release agent, 3 parts by mass of acid absorber, 2 parts by mass of accelerator, and 1 part by mass of vulcanizing agent;
[0088] S2, adding the rubber weighed in S1, yttrium oxide, internal mold release agent, acid absorber, accelerator, and vulcanizer to an open mill for mixing, the mixing temperature is 30-70°C, preferably 55°C, and mixing is uniform;
[0089] S3, vulcanizing the rubber mixture obtained in S2 into a sealing ring and a long sheet in a vacuum vulcanizer at a vulcanizing temperature of 170° C. and a vulcanizing time of 10 min;
[0090] S4. Place the sealing ring obtained in S3 in a blast oven for two-stage vulcanization at a vulcanization temperature of 230°C for 16 hours. The obtained sample is recorded as M0. The infrared test results are as follows: Figure 1 , the electron microscope image of the tensile fracture is as follows Figure 3 ;
[0091] S5. The obtained sealing ring and long sheet were tested for performance. The compression permanent deformation was tested according to ASTM D395 method B, and the tensile test was tested according to the method in ASTM D412. The test results are shown in Figure 2 .
[0092] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A modified fluororubber with high mechanical properties, characterized in that: It contains the following components in parts by mass: Fluororubber 80-120 parts by mass; 5-30 parts by mass of modified yttrium oxide; Internal release agent 0-8 parts by mass; Acid absorbent 0-10 parts by weight; Accelerator 0-8 parts by weight; Vulcanizing agent 0-8 parts by weight; The modified yttrium oxide is obtained by modifying yttrium oxide with a modifier, and the modifier includes one or more of TEOS, zinc oxide, and PFPE.
2. The modified fluororubber with high mechanical properties according to claim 1, characterized in that: The modifier includes zinc oxide and PFPE.
3. The modified fluororubber with high mechanical properties according to claim 1, characterized in that: The modifiers include TEOS, zinc oxide and PFPE.
4. The modified fluororubber with high mechanical properties according to claim 3, characterized in that: The preparation of the modified yttrium oxide comprises the following steps: S1. Dissolving yttrium oxide in a solvent to obtain a mixed solution L1; S2. Add aqueous ammonia to the mixed solution L1 and stir for 0-1h to obtain a mixed solution L2; S3. Add zinc oxide to the mixed solution L2 and stir at 50-70 ° C for 1-3 h to obtain a mixed solution L3; S4. Add PFPE to the mixed solution L3 and stir at 80-120°C for 20-28h to obtain a mixed solution L4; S5. TEOS was added to the mixed solution L4 and stirred at 30-60°C for 4-8h to obtain a mixed solution L5; S6. Wash, centrifuge and dry the mixed solution L5 to obtain modified yttrium oxide.
5. The modified fluororubber with high mechanical properties according to claim 4, characterized in that: The mass volume ratio of the zinc oxide, PFPE and TEOS is 1:8-12:8-12.
6. The modified fluororubber with high mechanical properties according to claim 1, characterized in that: The fluororubber is perfluoroether rubber.
7. The modified fluororubber with high mechanical properties according to claim 1, characterized in that: The internal mold release agent is one or more of HT290 and WS280; the acid absorber is one or more of zinc oxide, magnesium oxide, and sodium hydroxide; the vulcanizing agent is one or more of dipentadienyl, triazine trithiol tetrabutylammonium salt, and BOAP.
8. The modified fluororubber with high mechanical properties according to claim 1, characterized in that: It contains the following components in parts by mass: 100 parts by mass of fluororubber; 10 parts by mass of modified yttrium oxide; 1 part by mass of internal release agent; 3 parts by mass of acid absorbent; 2 parts by mass of accelerator; 1 part by mass of vulcanizing agent.
9. The method for preparing the modified fluororubber according to any one of claims 1 to 8, characterized in that: The steps include: (1) Weigh the raw materials according to mass fraction; (2) drying the raw materials in step (1), adding them into an open mill and mixing them at a mixing temperature of 35-75° C., and mixing them evenly to obtain a rubber compound; (3) subjecting the rubber compound obtained in step (2) to a curing process in a vulcanizer at a temperature of 155-205° C. for a time of 8-12 min; (4) The material obtained by vulcanization in step (3) is placed in a blast oven for two-stage vulcanization at a vulcanization temperature of 185-305° C. and a vulcanization time of 8-24 h.
10. A fluororubber sealing ring, the main material of which is the modified fluororubber according to any one of claims 1 to 8.
Citation Information
Patent Citations
0-shaped PTFE fluoropolymer ring and production technology thereof
CN109294126A
Modified fluororubber sealing ring and preparation method thereof
CN116478492A
Process for improving deformation rate of sealing ring of cylindrical lithium battery safety helmet
CN117624932A